The non-linear relationship between triglyceride-glucose index and risk of chronic kidney disease in hypertensive patients with abnormal glucose metabolism: A cohort study - Zhu, Qing; Chen, Yuan; Cai, Xintian; Cai, Li; Hong, Jing; Luo, Qin; Ren, Yingli; Guo, Yanying; Li, Nanfang (Frontiers in Medicine, 2022)
Background: Triglyceride–glucose (TyG) index has been reported to be associated with cardiovascular disease. However, few studies have focused on TyG index and the risk of chronic kidney disease (CKD). Thus, this study aims to explore the relationship between TyG index and CKD. Methods: 2033 participants with hypertension between January 2012 and May 2019 were included in the longitudinal observational study. All patients are grouped according to the TyG index quartile. CKD was defined as estimated glomerular filtration rate (eGFR)＜60 ml/min per1.73m2 and/or positive proteinuria. Multivariate Cox proportional hazards models were used to investigate the relationship between TyG index and CKD. Results: During a median follow-up of 31 months, 302 participants developed CKD, with a mean age of 55.5 years and median TyG of 8.94. Compared with those in the lowest quartile of TyG index, participants in the highest quartile of TyG index exhibited 1.63-fold higher hazard ratio (95%CI: 1.14-2.33, P=0.007) for presence of CKD. And restricted cubic spline analysis showed the relationship between TyG index and CKD is nonlinear (P non-linearity=0.021). The hazard ratio for CKD first fell and after rising until around 8.94 of TyG index and started to increase rapidly afterwards (P for TyG ＜0.001). Conclusion: Higher TyG index is associated with the increased risk for CKD. Early intervention of metabolic factors may prevent the occurrence of CKD, thereby reducing the incidence of cardiovascular disease and premature death.